Livelihood Responsibility Shifting to Migrant Worker Wives; A Reading of Qur’an and Hadith in Muslim Community - Khamim, Khamim; Hijriyati, Muthiah; Ansori, Ibnu Hajar; Mohammad Hamsa Fauriz (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This article aims to explore the shifting of livelihood (nafqa) responsibilities from husbands to wives in the contemporary context while looking at Muslim community’s reading on relevant Qur’an verses and hadith. Wives who work as migrant workers tend to serve as the main breadwinner in providing income in a household, including those from Kediri and Tulungagung, East Java. Livelihood itself is a common topic in the Islamic law discussion, mainly about who provide for whom and its quantity criteria. Based on this problem, we portray the phenomenon and then present a reading of relevant Qur’anic verses and hadith within the community. The qualitative method was used by conducting interviews with husbands situated in that specific type of household. Data collection was also carried out by a review of relevant verses and hadith on family life followed by analytical approach using content analysis to identify how they are perceived by Muslim community. This study offers insights into Islamic family law in contemporary society, linking religious teachings to modern realities and providing a deeper understanding of this complex issue. The result shows that despite the phenomenon, the husbands still play their role as breadwinners, namely the secondary one. This stems from how they understand the rule of each family party, implying how religious teachings interplay with modern realities.